Dual targeting of HER3 and EGFR in colorectal tumors might overcome anti-EGFR resistance. (May 2016) - Temraz, Sally; Mukherji, Deborah; Shamseddine, Ali
Abstract: Multiple genetic alterations have been associated with resistance to anti–EGFR therapy in metastatic colorectal cancer (CRC) patients. Research has been mainly focused on driver mutations in KRAS, NRAS, BRAF and PI3K. However, recent evidence suggests a crucial role for non-genetic mechanisms in conferring resistance to anti-EGFR therapy. Specifically, the HER3 receptor is capable of heterodimerizing with multiple EGFR family members resulting in downstream activation of the PI3K and MAPK pathways. Monoclonal antibodies targeted against the HER3 receptor are being investigated in clinical trials; however, preliminary data has shown limited clinical activity. Thus, given the relevance of the HER3 receptor in activating downstream effector pathways and in conferring resistance to anti-EGFR therapy, the therapeutic targeting of HER3 in combination with primary drivers of the tumor is also being investigated. Here, we review the role of HER3 as a promoter of clinical resistance to EGFR therapy and discuss therapeutic approaches that could potentially overcome this resistance.